Pt accelerated coarsening of A15 precipitates in Cr-Si alloys. (June 2022) - Ulrich, Anke S.; Knowles, Alexander J.; Cantatore, Valentina; Bhowmik, Ayan; Wharmby, Michael T.; Geers, Christine; Panas, Itai; Galetz, Mathias C.
Graphical abstract: Highlights: Pt enhances coarsening of A15 precipitates in Cr-rich Cr-Si-alloys. A ternary Cr-rich Cr-Si-Pt phase diagram at 1200°C is proposed. Pt causes Cr ss /A15 interface distortion A rim of enhanced Pt concentration destabilizes the Pt-containing A15 precipitates. The coarsening mechanism differs between Pt-rich and Pt-lean precipitates. Abstract: The effect of alloying Cr-rich Cr-Si alloys with Pt was investigated by a combination of complementary experimental methods and atomic scale modelling. The investigated Cr-Si and Cr-Si-Pt (Cr ⩾ 86 at.%) alloys developed a two-phase microstructure consisting of Cr solid solution ( Cr ss ) matrix and strengthened by A15 precipitates during annealing at 1200°C. It was found that additions of 2 at.% Pt increase the coarsening rate by almost five times considering annealing times up to 522 h. Pt was found to change the precipitate matrix orientation relationship, despite its low influence on the Cr ss matrix/A15 precipitate misfit. Through this experimental and modelling approach new insight has been gained into mechanisms of enhanced coarsening by Pt addition. The increased coarsening is principally attributed to a change in interface composition and structure resulting in different thermodynamic stabilities: Pt-containing A15 phase was found to have a broader compositional range if both elements, Pt and Si, are present compared to only Si. Additionally, the Cr ss phase was found to have a higher solubility of Pt and Si over just Si. Both factors additionally facilitated Ostwald ripening.